New psychoactive substances: an overview on recent publications on their toxicodynamics and toxicokinetics - Meyer, Markus Robert (Archives of toxicology, 2016)
This review article covers English-written and PubMed-listed review articles and original studies published between January 2015 and April 2016 dealing with the toxicodynamics and toxicokinetics of new psychoactive substances. Compounds covered include stimulants and entactogens, synthetic cannabinoids, tryptamines, NBOMes, phencyclidine-like drugs, benzodiazepines, and opioids. First, an overview and discussion is provided on timely review articles followed by an overview and discussion on recent original studies. Both sections are then concluded by an opinion on these latest developments. This review shows that the NPS market is still highly dynamic and that the data published on their toxicodynamics and toxicokinetics can hardly keep pace with the appearance of new entities. However, data available are very helpful to understand and predict how NPS may behave in severe intoxication. The currently best-documented parameter is the in vitro metabolism of NPS, a prerequisite to allow detection of NPS in biological matrices in cases of acute intoxications or chronic consumption. However, additional data such as their chronic toxicity are still lacking.